Deep Electrical Structure of the Langshan Mountain-Linhe Basin Area on the Northwest Edge of the Ordos Block, China - Zhao, Lingqiang; Wang, Qingliang; Cao, Cong; Hao, Ming (Frontiers in Earth Science, 2022)
A series of fault depression structures have developed around the Ordos Block. The Langshan Mountain-Linhe Basin area (LLA), located on the northwest edge of the Ordos Block, is a typical, normal tension fault system. A geological survey shows that the Langshan Piedmont fault (LPF) in this area has a large slip rate and indicates risk of earthquake preparation. Broadband magnetotelluric (MT) exploration research was recently carried out across the LLA in the NW–SE direction, and the three-dimensional deep electrical structure thus obtained revealed that the LPF in the LLA is an evident electrical boundary zone on the whole crustal scale and is the main boundary fault of the primary structural block of the Alxa and Ordos Blocks. The MT results also show that the Linhe Basin and Ordos Block belong to the same tectonic basement. The Linhe and Dengkou faults belong to the internal faults of the Ordos Block. The upper crust of the Langshan Mountain on the west side of LPF is characterized by high-resistivity, the middle and lower crust have a low-resistivity layer, and the Linhe Basin on the east side has a Cenozoic low-resistivity sedimentary layer of approximately 10 km thick, which reveals that the Linhe Basin is a faulted basin with sedimentary thickness around the Ordos Block. This indicates that the LLA has experienced continuous and strong tension, normal fault depression sedimentary activities since the Cenozoic era. The current Global Positioning System velocity field shows that there is an apparent NW–SE acceleration zone in the LLA. The leveling data indicate that Linhe Basin shows a subsidence trend relative to the Ordos Block, indicating that the area is undergoing continuous NW–SE tension and faulting. It is speculated that there is a risk of earthquake preparation in the LPF.